Análisis de la producción y comercialización de tres abonos orgánicos en el Ecuador. - Zúñiga Zhispon, Kevin Alexander (2022)
Organic fertilizers have now become a viable alternative to develop healthy agricultural production, however, currently the organic fertilizers existing within the market sometimes do not meet the demand, which as a consequence causes farmers to use chemical fertilizers to improve production in their crops. The main objective of the research topic was to carry out an "Analysis of production and commercialization of three organic fertilizers in Ecuador". In the analysis that was made about the supply and production, showed that in the country there is in a certain way a great unsatisfied demand, that currently the companies dedicated to the production and commercialization of organic fertilizers do not satisfy it.